The Role of the Minister of Tourism and Creative Economy in Encouraging Innovation and Entrepreneurial Networks in the Creative Economy Sector in Indonesia - Erny Rachmawati; Jamaluddin Majid; Chevy Herli Sumerli A.; Roosganda Elizabeth (West Science Journal Economic and Entrepreneurship, 2023)
The creative economy has become a driving force for economic growth and cultural development in Indonesia, with the Minister of Tourism and Creative Economy at the forefront of shaping policies and initiatives to support this sector. This research employs a mixed-methods approach, combining quantitative survey data and qualitative insights from in-depth interviews, to explore the Minister's role in encouraging innovation and entrepreneurial networks in the creative economy. The findings reveal a generally positive perception of the Minister's policies, with stakeholders acknowledging their effectiveness in promoting innovation and entrepreneurial networks. Networking and collaboration initiatives facilitated by the Minister are seen as instrumental in fostering connections within the sector. While challenges exist, including the need for enhanced funding accessibility and intellectual property protection, they present opportunities for policy improvement. The study contributes to a nuanced understanding of the Minister's impact and offers policy recommendations to further enhance the growth and sustainability of the creative economy in Indonesia.